Utilizing Data Analytics to Enhance Software Product Development in the Finance Industry: An Applied Framework - Iyer, Uma (Digital Repository of Theses, 2024)
This dissertation explores how data analytics can improve software product development in the finance industry. With the rapid growth of data generated by financial institutions, there is immense potential to use this data to gain valuable insights, predict trends, mitigate risks, and optimize decision-making. The study investigates the role of data analytics in enhancing various aspects of financial software development, including design, user experience, operational efficiency, security, and regulatory compliance. The research underscores the unique needs of the finance sector, such as risk management, customer insights, compliance with stringent regulations, investment decision-making, and operational efficiency. It emphasizes the value of tailoring software solutions to these needs by integrating advanced data analytics techniques. By doing so, financial institutions can leverage data analytics to develop more innovative, competitive, and user-friendly software products, thereby enhancing their operations and services. The study also addresses the challenges faced by financial institutions when incorporating data analytics into their software development processes. These challenges include ensuring data quality and accuracy, integrating legacy systems, maintaining data security and privacy, adhering to regulatory requirements, and managing scalability. The dissertation proposes practical strategies to overcome these obstacles, such as adopting robust data governance frameworks to ensure data quality, utilizing scalable cloud-based solutions to manage scalability, and investing in continuous training and development programs for employees to maintain data security and privacy. Quantitative data collection and analysis, Surveys and secondary data analysis are employed to gather insights from industry professionals, and statistical methods are used to measure the impact of data analytics on various aspects of software development. The findings demonstrate that data analytics significantly enhances software product development in the finance industry by improving decision-making, operational efficiency, user satisfaction, security, and regulatory compliance. The dissertation concludes by providing a comprehensive framework for effectively integrating data analytics into the software development lifecycle. It also suggests avenues for future research, including exploring advanced machine learning and AI techniques, real-time data analytics, ethical considerations, and cross-industry comparisons. Ultimately, the study highlights the transformative potential of data analytics in financial software development and its role in driving innovation, competitiveness, and growth in the finance sector.